Predictor-corrector scheme for solving second order ordinary differential equations - Mohamat Johari, Mohamat Aidil; Abdul Majid, Zanariah (Malaysian Mathematical Science Society, 2022)
In this research, the direct method of Adam Moulton two-step method was proposed for solving initial value problem (IVPs) of second order ordinary differential equations (ODEs) directly. The current approach for solving second order ODEs is to reduce to first order ODEs. However, the direct method in this research will solved the second order ODEs directly. The Lagrange interpolation polynomial was applied in the derivation of the proposed method. The implementation will be in predictor-corrector scheme. Numerical results shown that the method gave comparable accuracy and faster execution time compared to the existing method. The proposed direct method of Adams Moulton type is suitable for solving second order ODEs.